Randomized comparison of renal effects, efficacy, and safety with once-daily abacavir/lamivudine versus tenofovir/emtricitabine, administered with efavirenz, in antiretroviral-naive, HIV-1-infected adults: 48-week results from the ASSERT study - Post, F (2011)
BACKGROUND: Abacavir/lamivudine and tenofovir/emtricitabine fixed-dose combinations are commonly used first-line antiretroviral therapies, yet few studies have comprehensively compared their safety profiles. METHODS: Forty-eight-week data are presented from this multicenter, randomized, open-label study comparing the safety profiles of abacavir/lamivudine and tenofovir/emtricitabine, both administered with efavirenz, in HLA-B*5701-negative HIV-1-infected adults. RESULTS: Three hundred eighty-five subjects were enrolled in the study. The overall rate of withdrawal was high (28%). Changes in estimated glomerular filtration rate from baseline were similar between arms [difference 0.953 mL.min.1.73 m (95% confidence interval: -1.445 to 3.351), P = 0.435]. Urinary excretion of retinol-binding protein and beta-2 microglobulin increased significantly more in the tenofovir/emtricitabine arm (+50%; +24%) compared with the abacavir/lamivudine arm (no change; -47%) (P < 0.0001). A lower proportion achieved viral load <50 copies per milliliter in the abacavir/lamivudine arm (114 of 192, 59%) compared with the tenofovir/emtricitabine arm (137 of 193, 71%) [difference 11.6% (95% confidence interval: 2.2 to 21.1)]. The overall virological failure rate was low. The adverse event rate was similar between arms (except drug hypersensitivity, reported more in the abacavir/lamivudine arm). CONCLUSIONS: The study showed no difference in estimated glomerular filtration rate between the arms, however, increases in markers of tubular dysfunction were observed in the tenofovir/emtricitabine arm, the long-term consequence of which is unclear. A significant difference in efficacy favoring tenofovir/emtricitabine was observed.